From Iconoclastic to Tradition: The Changes of Female Aesthetics by Cao Yu （由反传统到传统一一论曹禺女性审美观的逆转 ） - æé“¶, æ›¾; æƒ æ€, å¼ (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2015)
Abstract The changes of female aesthetics from iconoclastic to tradition by Cao Yu can be seen in the drama he wrote from the beginning until the period of anti-Japanese War. The female characters in drama he wrote in the beginning are filled with passion, wild and rebellious; they comply with themselves, contempt for all things related to old feudal system. They are also women who dare to love or hate, and they have rebellious spirit of destroying the outdated conventional ideas. Examples of the female characters that show the above qualities are Fan Yi (繁漪） and Chen Bailu (陈白露) . However, after the year of 1938, during the period of anti-Japanese War, the female characters tend to be Chinese traditional and classical in Cao Yu's drama. The characters best illustrates the above quality in his drama include Ding Dafu（丁大夫） , Wei Ming (韦明 ) and Rui Jue ( 瑞玉) . Therefore, this article will be based on the ideal personality of Confucius' views and the specifications book which contains behavioral norms for women in Confucian ethics, trying to analyze the changes of female characters in Cao Yu's drama from iconoclastic to tradition. On the other hand, this article will also explore the reasons for the changes of female aesthetics by Cao Yu through historical background and marital status during his lifetime. 摘要 曹禺在抗日战争爆发之前，即I 933年至1937年之间共创作了三部作品，那就是 《雷雨》、《日出》以及《原野》，本文把它称之为前期创作。而1938年抗日战 争这段期间，曹禺也写了不少代表作品，如《蜕变》、《黑字二十八》、《北京 人》和《家》。从前期到抗日战争时期的剧作中可看出曹禺对女性审美观的差 异，象征着一种由反传统向传统的逆转。前期剧作的女性洋溢着生命激情、充满 了叛逆、狂野的气息，她们遵从自我、藐视一切与旧伦理有关的事物，且饱含着 敢爱敢恨及富有反传统的抗争精神，其中具有代表性的女性角色有蔡漪和陈白 露。1938年后的抗战时期，其作品中的女性形象却转而趋向于以传统、古典的美 为标准，当中包括了丁大夫、韦明和瑞环。因此，本文将以古代儒家对理想人格 的标准以及儒家所标榜的女性行为规范著作为依据，探讨曹禺笔下女性由反传统 到传统的逆转。接着，本文将结合作者的所处的时代背景与个人经历来分析曹禺 对女性审美逆转的缘由。